THE EFFECT OF EXTRACTION METHODS ON TOTAL FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY USING THE ABTS METHOD (2,2-AZINOBIS (3-ETHYLBENZOTHIAZOLINE)-6-SULFONIC ACID) IN SEAGRASS LEAF EXTRACT (ENHALUS ACOROIDES (L. F.)) - WIDYANINGRUM, NANIEK; RAHMADANI, AZMI; SAKURA, ALYA PUTRI; ARIEF, THENDI ABDUL (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to determine the effect of different extraction methods on flavonoid levels and antioxidant activity in seagrass leaves (Enhalus acoroides), with a particular focus on assessing their potential as natural antioxidants. Methods: Flavonoids were extracted using infusion and ultrasonic methods with various solvents, including distilled water, ethyl acetate, and n-hexane. Flavonoid levels were measured in mg QE/g, while antioxidant activity was evaluated using the ABTS assay, with IC₅₀ values determined using a UV-Vis spectrophotometer. Data were analyzed using several statistical tests, including the Shapiro-Wilk normality test, Levene's homogeneity test, t-test, Kruskal-Wallis test, Mann-Whitney test, ANOVA, and correlation analysis. Results: The flavonoid content varied depending on the extraction method and solvent used: 4.339 mg QE/g for infusion with distilled water, 8.777 mg QE/g for ultrasonic distilled water, 68.836 mg QE/g for ethyl acetate, and 6.61 mg QE/g for n-hexane. Antioxidant activity results showed IC₅₀ values of 13.76 µg/ml for ultrasonic distilled water, 13.66 µg/ml for ethyl acetate, and 15.59 µg/ml for n-hexane. The highest flavonoid levels were observed in the ethyl acetate extract. Statistical analysis confirmed that the extraction method significantly influenced flavonoid content. Conclusion: Seagrass leaf extract obtained using ethyl acetate solvent showed the highest flavonoid concentration and potent antioxidant activity. The antioxidant activity of this extract was comparable to that of vitamin C, classifying it as a strong natural antioxidant. The findings support the importance of extraction method and solvent selection in optimizing bioactive compound yield and activity.